New insights into the composition and catalytic performance of VOx-Ga/γ-Al2O3 for the oxidative dehydrogenation of propane to propene - Kandasamy, Prabu; Gawali, Sheetal; Venugopalan, Aswathy Thareparambil; Manikandan, Marimuthu; Mekala, Siva Prasad; Shelke, Ankita; Ajithkumar, Thalasseril G.; Bhatte, Kushal; Raja, Thirumalaiswamy (New Journal of Chemistry, 2024)
Oxidative dehydrogenation (ODH) of propane is a promising alternative route for propene production. In this work, we developed a series of vanadium and gallium oxides supported on gamma-Al2O3 catalysts by an incipient wetness impregnation method. Among the employed catalysts, the VGA-2 showed superior catalytic activity, and the catalyst was demonstrated for longevity in ODH of propane with a stable activity using a continuous flow fixed bed reactor at 400 degrees C. H-2-TPR and UV-visible spectra showed the presence of highly dispersed monomeric VOx species with tetrahedral coordination geometry, which influences product selectivity. The characterization results also conferred that the redox nature of vanadium (V5+ and V4+) oxide and higher V5+ content on the surface of the VGA-2 catalysts are more favourable for C-H activation. In addition, the pyridine-FTIR and Ga-71 solid-state NMR studies further substantiated the presence of Lewis acid sites and tetrahedrally coordinated Ga3+Ox species that are highly responsible for the ODHP activity, respectively. Furthermore, in situ-DRIFTS studies conferred that the propane adsorption at ambient temperature showed the formation of intermediate propoxide species with the evolution of sigma-bonds and with further increase in the temperature to 325 degrees C; the stretching vibrations of the =C-H and -C-H bonds in the propylene molecule were observed. The spent catalysts were also analyzed by thermogravimetric analysis, where the optimized catalyst (VGA-2) showed the least coke deposition.